MEMBANGUN KOMPETENSI EKOLOGIS MELALUI EKOPEDAGOGI DALAM PENDIDIKAN AGAMA KATOLIK - alek martin pakpahan; Mariana Siregar; Fransiskus Tarigan (STP St. Bonaventura Medan, 2025)
The global environmental crisis calls for the integration of religious values and ecological awareness in education. This study explores the implementation of ecopedagogy in Catholic religious education to enhance students' ecological competencies. Using a qualitative case study approach in selected schools, the research investigates how religious education can incorporate environmental values rooted in Catholic teachings. The findings show that ecopedagogy positively influences students' knowledge, attitudes, skills, and participation in environmental conservation. Programs like the Green School initiative have improved students’ ecoliteracy, though further efforts are needed to internalize sustainable behaviors. Integrating religious teachings with ecopedagogical principles enriches students’ spiritual formation and fosters critical environmental awareness. The success of such integration relies on consistent strategies and strong collaboration among teachers, students, and the community. These partnerships enhance the relevance and impact of ecopedagogical learning experiences. The study recommends developing interactive and contextual ecopedagogical programs, increasing stakeholder involvement, and ensuring environmental education is embedded across all school activities. Policy support is also essential to sustain and scale these efforts. Overall, the research highlights that ecopedagogy in religious education is a powerful approach to nurture both spiritual growth and ekologi.